Initial growing, phosphorus critical levels and phosphate fractions in forest species - Fernandes, Luiz Arnaldo; Neto, Antonio Eduardo Furtini; Fonseca, Fernando Cavicchioli; Vale, Fabiano Ribeiro do (Pesquisa Agropecuaria Brasileira, 2000)
An experiment under greenhouse conditions was carried out at Universidade Federal de Lavras, Minas Gerais State, Brazil, to evaluate the growth of seedlings, phosphorus critical levels and phosphate fractions, in forest species growing under four phosphorus levels. Seedlings of Schinus terenbinthifolius Raddi (aroeirinha), Chorisia speciosa St. Hill. (paineira) and Syzygium jambolanum Lam. (jambolão) were cultivated on an Oxisol fertilized with 0, 150, 300 and 600 mg dm-3 of P. The seedlings were harvested 180 days after germination and analysed for P forms. In all levels of phosphorus addition, the paineira produced higher aerial and root biomass than aroeirinha and jambolão, and presented higher contents of organic phosphorus and higher relative participation of organic phosphorus in the total acid soluble phosphorus under all phosphorus levels. The improved growth rate of paineira was attributed to a greater efficiency in the metabolic adjustments of this species in relation to phosphorus nutrition, indicating that this species can grow in soils of variable P levels.
Keywords: Schinus terenbinthifolius; Chorisia speciosa; Syzygium jambolanum; seedlings; phosphate fertilizers; plant soil relations